2012
DOI: 10.1111/j.1365-2982.2012.01948.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of transient hiatus hernia during transient lower esophageal sphincter relaxations and swallows in healthy subjects

Abstract: The marked proximal GEJ migration during TLESRs represents very severe herniation of the GEJ. The rapid initial return of the GEJ following TLESRs when the crural diaphragm is relaxed and its correlation with amplitude suggest it is due to elastic recoil of the phreno-esophageal ligament. The marked stretching of the phreno-esophageal ligament during TLESRs may contribute to its weakening and development of established hiatus hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Assuming that the acid pocket migrates upwards with the LES, a situation comparable to a hernia would result promoting acid refl ux. In fact, continuous postprandial monitoring of the location of the EGJ in healthy volunteers confi rmed that during TLESRs there was marked proximal movement of the EGJ by a median of 4.3 cm, representing signifi cant herniation ( 46 ). Th e Bredenoord and Beaumont studies also reported that spatial separation between the LES and crural diaphragm increases the risk ( 19 ).…”
Section: Acid Pocket and Hiatus Herniamentioning
confidence: 84%
“…Assuming that the acid pocket migrates upwards with the LES, a situation comparable to a hernia would result promoting acid refl ux. In fact, continuous postprandial monitoring of the location of the EGJ in healthy volunteers confi rmed that during TLESRs there was marked proximal movement of the EGJ by a median of 4.3 cm, representing signifi cant herniation ( 46 ). Th e Bredenoord and Beaumont studies also reported that spatial separation between the LES and crural diaphragm increases the risk ( 19 ).…”
Section: Acid Pocket and Hiatus Herniamentioning
confidence: 84%
“…Swallowing motion can be analyzed and quantified by kinematic data using motion analysis (Paik et al, 2008), kinetic data using manometry (Lee et al, 2012), and muscle activities using dynamic electromyography (Yu et al, 2013) can be easily performed by videofluoroscopic swallowing studies (VFSS) without any discomfort, contrary to kinetic and electromyographic analyses, which cause substantial discomfort. Moreover, the extent and pattern of the hyoid bone and the epiglottis movement revealed by kinematic analysis can differentiate etiologies of dysphagia and suggest the mechanism of dysphagia (Paik et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…More recent evidence, using a novel Hall-effect technique that allows continuous measurement of the location of the GEJ without the need for fluoroscopy, indicates that TLESRs are a severe but transient form of hiatus herniation 4,5. Furthermore, partial hiatus hernia is likely to be common especially in the presence of obesity and raised intra-abdominal pressure 6.…”
Section: To the Editormentioning
confidence: 99%